Building a Zero-Carbon Economy: SCCS evidence - Bell, Rebecca; Brownsort, Peter (SCCS, 2018)
Scottish Carbon Capture & Storage (SCCS) is a research partnership of the British Geological Survey (BGS), Heriot-Watt University, University of Aberdeen, the University of Edinburgh and the University of Strathclyde with associate member the University of St Andrews. SCCS researchers are engaged in innovative applied research and joint projects with industry and government to support the development and commercialisation of carbon capture and storage as a climate change mitigation technology. SCCS is pleased to submit evidence to the Committee on Climate Change on how carbon capture and storage, carbon dioxide utilisation, and negative emissions technologies can contribute to building a zero-carbon economy.
Keywords: CCS; Zero-carbon economy